THE FUTURE OF DEMOCRACY IN DEVELOPING COUNTRIES: A STUDY ON LEGISLATIVE AND JUDICIARY RELATIONS - Aluko Aluko; Opeyemi Idowu (Journal of Social Political Sciences, 2023)
The beauty of democracy is freedom of expression that promotes growth and development in the country. Cooperation among the various arms of government is vital to sustainable development of democracy. Governance process will be in total chaos if the arms of government are totally independent of one another. The extent of interdependency is the extent of unity and progress. The collaboration however must have basic limitations so as to prevent the fusion of governmental powers into one hand. If these roles are jeopardised the political system might relapse into anarchy. In developing countries, the extent of cooperation or distinction is not certain if they are present at all. Therefore the research questions posed are; what are the areas of collaborations of legislative-judicial relations in developing countries and how can they be improved. Institutionalism theoretical framework analysis is adopted. The study concludes on the premise that good governance, accountability and transparency in the daily operations of the two arms of government are inevitable to national development in developing countries.